2008
DOI: 10.5551/jat.e543
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Detection of Oxidative Stress Biomarkers, Dityrosine and N&sup.EPSILON.;-(hexanoyl)lysine, and C-Reactive Protein in Rabbit Atherosclerotic Lesions

Abstract: Several lines of evidence have demonstrated that C-reactive protein (CRP) is associated with oxidative stress; however, the precise co-localization between CRP and oxidative stress markers in atherosclerotic lesions is not fully established. In this study, we focused on two oxidative stress markers, dityrosine (DY) and N -(hexanoyl)lysine (HEL), which had not previously been investigated in relation to CRP in atherosclerotic lesions. Aim: We investigated the production and localization of DY, HEL, and CRP in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 32 publications
1
42
0
Order By: Relevance
“…As for the mechanisms, Fukuchi, et al 32) reported the immunohistochemical detection of oxidative stress biomarkers, dityrosine and N -(hexanoyl)lysine, and C-reactive protein in rabbit atherosclerotic lesions.…”
Section: Discussionmentioning
confidence: 99%
“…As for the mechanisms, Fukuchi, et al 32) reported the immunohistochemical detection of oxidative stress biomarkers, dityrosine and N -(hexanoyl)lysine, and C-reactive protein in rabbit atherosclerotic lesions.…”
Section: Discussionmentioning
confidence: 99%
“…CRP is bound to the membranes of damaged vascular cells where it activates complement proteins or enhances the production of thrombogenic agents. These instances of vascular inflammation may contribute to the development of insulin resistance 30,31) . Insulin resistance and vascular inflammation may create a vicious cycle in vivo 7) .…”
Section: Fig 2 Relationships Of Hs-crp To Fasting Iri In Nonsmokersmentioning
confidence: 99%
“…The second marker was N-epsilon-(hexanoyl)-lysine (HEL), which has attracted attention as a marker of early stage lipid peroxidation. HEL is associated with rheumatoid arthritis and arteriosclerosis (Fukuchi et al, 2008;Kageyama et al, 2008). Some recent studies have shown that the intake of foods containing anti-oxidants reduces 8-OHdG ( Thompson et al, 1999;Dhawan and Jain, 2005), but there have been only a few studies on the 8-OHdG level after kiwi fruit intake (Collins and Harrington, 2003) and no study on HEL.…”
Section: Introductionmentioning
confidence: 99%